Comprehensive Assessment: Balancing Test and Non-Test Methods in Islamic Education Evaluation - Abdurahman, Asep; Erihadiana, Mohamad (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2024)
The forms of test and non-test assessments have become a widely discussed topic in the field of The method used is a literature review, sourcing data from relevant books and scholarly articles. The test technique involves questions or tasks that students must answer, which are categorized into objective tests and subjective tests (essay). Meanwhile, the non-test evaluation technique is employed to assess students’ personalities comprehensively, covering attitudes, behaviors, characteristics, social attitudes, speech, and life history. The forms of non-test assessment include observation, interviews, attitude scales, questionnaires, and personal reports. This study highlights the importance of combining these two techniques for a more comprehensive evaluation.